Axi-Higgs cosmology. Issue 8 (25th August 2021) - Fung, Leo W.H.; Li, Lingfeng; Liu, Tao; Luu, Hoang Nhan; Qiu, Yu-Cheng; Tye, S.-H. Henry
Abstract: If the electroweak Higgs vacuum expectation value v in early universe is ∼ 1 % higher than its present value v0 =246 GeV, the 7 Li puzzle in BBN and the CMB/ΛCDM tension with late-universe measurements on Hubble parameter are mitigated. We propose a model of an axion coupled to the Higgs field, named "axi-Higgs", with its mass ma ∼ 10 -30 - 10 -29 eV and decay constant fa ∼ 10 17 - 10 18 GeV, to achieve this goal. The axion initial value aini yields an initial Δ vini /v0 ∼ 0.01 throughout the BBN-recombination epoch and a percent level contribution to the total matter density today. Because of its very large de Broglie wavelength, this axion matter density ωa suppresses the matter power spectrum, alleviating the CMB/ΛCDM S8 /σ8 tension with the weak-lensing data. It also explains the recently reported isotropic cosmic birefringence by its coupling with photons. Adding the axion (m ∼ 10 -22 eV) in the fuzzy dark matter model to the axi-Higgs model allows bigger Δ vrec and ωa to address the Hubble and S8 /σ8 tensions simultaneously. The model predicts that Δ v may be detected by the spectral measurements of quasars, while its oscillation may be observed in the atomic clock measurements.